Corpus callosum size and diffusion tensor anisotropy in adolescents and adults with schizophrenia. Issue 3 (30th March 2015) - Balevich, Emily C.; Haznedar, M. Mehmet; Wang, Eugene; Newmark, Randall E.; Bloom, Rachel; Schneiderman, Jason S.; Aronowitz, Jonathan; Tang, Cheuk Y.; Chu, King-Wai; Byne, William; Buchsbaum, Monte S.; Hazlett, Erin A.
Abstract: The corpus callosum has been implicated as a region of dysfunctional connectivity in schizophrenia, but the association between age and callosal pathology is unclear. Magnetic resonance imaging (MRI) and diffusion-tensor imaging (DTI) were performed on adults ( n =34) and adolescents ( n =17) with schizophrenia and adult ( n =33) and adolescent ( n =15) age- and sex-matched healthy controls. The corpus callosum was manually traced on each participant׳s MRI, and the DTI scan was co-registered to the MRI. The corpus callosum was divided into five anteroposterior segments. Area and anisotropy were calculated for each segment. Both patient groups demonstrated reduced callosal anisotropy; however, the adolescents exhibited reductions mostly in anterior regions while the reductions were more prominent in posterior regions of the adults. The adolescent patients showed greater decreases in absolute area as compared with the adult patients, particularly in the anterior segments. However, the adults showed greater reductions when area was considered relative to whole brain white matter volume. Our results suggest that the initial stages of the illness are characterized by deficiencies in frontal connections, and the chronic phase is characterized by deficits in the posterior corpus callosum; or, alternatively, adolescent-onset schizophrenia may represent a different or more severe form of the illness. Highlights: We examined the corpus callosum in adult and adolescent schizophrenia patients. Area and anisotropy were measured in the corpus callosum. Adolescents had reduced anisotropy and area, most markedly in the anterior region. Reductions in anisotropy were more prominent in posterior regions in the adults.